Sistem Pengaman Sepeda Motor Dengan RFID Berbasis IoT - Ananda Setia Wardana; Gigih Priyandoko; Dedi Usman Effendy (JURNAL APLIKASI DAN INOVASI IPTEKS "SOLIDITAS" (J-SOLID), 2022)
Motorcycles are a means of transportation that is widely used by various groups in society as a means of transportation. The number of types, models and brands of motorized vehicles is often the highlight and target of crime by the perpetrators of motorcycle theft. From the many cases of motorcycle theft ranging from the destruction of keyholes with latter T keys to liquids with chemicals, a motorcycle safety system with IoT-based RFID is needed to improve the motorcycle security system. The results showed that in a motorcycle safety system with IoT-based RFID, this test cut off the flow of motorcycle electricity located on the motorcycle coil using a relay controlled via android with the application getting the results as expected, the relay functions to disconnect the electric current properly and displays notifications on the Blynk application found on android. At an effective distance and slope so that the RFID Reader can read the RFID tag card is 0-1.5 cm with a tilt of 0-20°. The results of the IoT test the farthest distance in the wall-sealed scope is 1-26.10 meters, while the distance with the farthest open scope is 1-411.69 meters. This thesis is expected to contribute to the automotive world to improve the safety system on motorcycles when the vehicle is parked.